Talbot lithography: Self-imaging of complex structures - Isoyan, A.; Jiang, F.; Cheng, Y. C.; Cerrina, F.; Wachulak, P.; Urbanski, L.; Rocca, J.; Menoni, C.; Marconi, M. (Journal of vacuum science & technology. B, Microelectronics and nanometer structures processing, measurement and phenomena, 2009)
The authors present a self-imaging lithographic technique, capable of patterning large area periodic structures of arbitrary content with nanoscale resolution. They start from the original concept of Talbot imaging of binary gratings—and introduce the generalized Talbot imaging (GTI) where periodic structures of arbitrary shape and content form high-definition self-images. This effect can be used to create the complex, periodic patterns needed in the many lithographic fabrication steps of modern semiconductor devices. Since the process is diffraction limited, the achievable resolution depends only on the wavelength, mask patterning, and degree of coherence of the source. Their approach removes all the complex extreme ultraviolet (EUV) reflective masks and optics, replacing them with nanopatterned transmission masks and makes the whole process simple and cost effective. They have successfully verified the GTI concept using first a He–Ne laser, and then demonstrated its potential as a nanolithography method using a compact table-top soft x-ray (EUV) 46.9 nm laser source. These sources provide the high degree of coherence needed by diffraction-based imaging and are extendable to shorter wavelengths. They have recorded EUV GTI images up to the sixth Talbot plane, with consistent high quality good results, clearly demonstrating the ability of the GTI method to record high-resolution patterns at large distances.